Reasons Behind the Challenges Faced by Undergraduate Level Students While Communicating in English: Khulna University Perspective - Rabbi, Md. Fajlay; Kamal , Fairuz; Islam, Md. Sefatul Islam; Abir , Shahriar Shajid (Papanda Journal of English Education, 2025)
English is a required subject in the national curriculum of Bangladesh and pupils have to study English for twelve years. Even after twelve years of studying English, most of the pupils cannot speak English. Often it can be noted that tertiary-level students struggle when communicating in English in courses. Therefore, the study attempts to find out the challenges that the learners encounter in speaking English in the tertiary level courses.The study has conducted interviews with undergraduate students in almost every discipline of Khulna University. Students who were fresher in universities and studied basic courses in English were picked for the interview. In total, 40 individuals were chosen relying on opportunity sampling from various disciplines. Interview questions for the pupils were developed following the thesis objectives. Interview questions were translated into Bangla All interviews were done in Bangla. After a comprehensive investigation of qualitative techniques, suggestions have been offered for the learners and instructors.The gathered data were thematized and examined in terms of two broad categories: causes of Problems faced by students and Causes of Writing and Speaking Problems. The study studied mainly: personal, social, environmental, and language problems for speaking issues and teacher and teaching, course content, overuse of mother tongue, poor schooling, and classroom culture as the cause factors of speaking weakness. The study suggested building a positive setting, increasing student liberty, changing teaching practices, rewriting classes, and conducting speaking activities time and again.